2023
DOI: 10.1007/s00702-023-02595-9
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder and auditory sensory alterations: a systematic review on the integrity of cognitive and neuronal functions related to auditory processing

Abstract: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition with a wide spectrum of symptoms, mainly characterized by social, communication, and cognitive impairments. Latest diagnostic criteria according to DSM-5 (Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, 2013) now include sensory issues among the four restricted/repetitive behavior features defined as “hyper- or hypo-reactivity to sensory input or unusual interest in sensory aspects of environment”. Here, we review auditory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 196 publications
1
11
0
1
Order By: Relevance
“…However, it is unclear whether modulating concentration of these neurotransmitters may improve the pathological functional network connectivity or the behavioral phenotype. Thus, consistent with the suggestion of Gonçalves and Monteiro ( 29 ), in their recent review, the current study utilizes an experimental therapeutics approach and collects measures of E/I balance (magnetic resonance spectroscopy (MRS) GABA and glutamate concentrations), network connectivity (resting state and language task-related fMRI and diffusion weighted imaging (DWI)), magnetoencephalography (MEG) measures of auditory processing to attempt to develop a nomological network linking measures of E/I balance to measures of brain network connectivity and functioning to behavior.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is unclear whether modulating concentration of these neurotransmitters may improve the pathological functional network connectivity or the behavioral phenotype. Thus, consistent with the suggestion of Gonçalves and Monteiro ( 29 ), in their recent review, the current study utilizes an experimental therapeutics approach and collects measures of E/I balance (magnetic resonance spectroscopy (MRS) GABA and glutamate concentrations), network connectivity (resting state and language task-related fMRI and diffusion weighted imaging (DWI)), magnetoencephalography (MEG) measures of auditory processing to attempt to develop a nomological network linking measures of E/I balance to measures of brain network connectivity and functioning to behavior.…”
Section: Introductionsupporting
confidence: 93%
“…Early descriptions by Kanner ( 28 ) highlight aspects of language and language processing as core symptoms of the disorder. Though the current DSM-5 diagnostic criteria does not explicitly list auditory or language processing as a core symptom, alterations in perceptual processing, specifically in the auditory domain have been established across multiple levels of analysis and have been related to not only the social and communication symptoms of ASD, but also the restricted and repetitive behavior domain ( 29 ) though the directionality of this relationship is still up for debate ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the visual system, individuals with ASD also seem to display disruptions in auditory processing, without having hearing deficits [99]. Sound is a fundamental sensory cue to provide critical information regarding potential threats.…”
Section: Sensorial Triggeringmentioning
confidence: 99%
“…They analyzed questionnaires, imaging, and behavioral and electrophysiologic studies to gain insight on this topic. ABR studies showed that a portion of the cohort had longer latency, although this was not consistent across all stages of development, and EEGs showed unstable neural tracking in subcortical auditory processing [ 54 ]. They showed that those with ASD had an improved auditory perceptual capacity in conjunction with a reduced auditory discrimination and detection [ 54 ].…”
Section: Auditory Processing Disorders In Asdmentioning
confidence: 99%
“…ABR studies showed that a portion of the cohort had longer latency, although this was not consistent across all stages of development, and EEGs showed unstable neural tracking in subcortical auditory processing [ 54 ]. They showed that those with ASD had an improved auditory perceptual capacity in conjunction with a reduced auditory discrimination and detection [ 54 ]. The deficits that were seen seemed to be correlated with the severity of language impairment as well as social impairment.…”
Section: Auditory Processing Disorders In Asdmentioning
confidence: 99%